2006
DOI: 10.1182/blood-2005-10-4043
|View full text |Cite
|
Sign up to set email alerts
|

Detection of serum hepcidin in renal failure and inflammation by using ProteinChip System

Abstract: Hepcidin, a key regulator of iron metabolism, is expressed in the liver, distributed in blood, and excreted in urine. However, to date, no reliable and practical method for measuring the bioactive form of hepcidin in serum has been developed. Here, we used surface-enhanced laser desorp-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
233
3
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 264 publications
(273 citation statements)
references
References 32 publications
(55 reference statements)
31
233
3
6
Order By: Relevance
“…7 Also, the ELISA used to measure the serum Hepc concentration was not specific for biologically active Hepc-25. 30,49 No practical assay has been reported for measurement of active Hepc-25, although attempts have been made to develop an assay system by using SELDI-TOF MS. 50 Hjv gene expression could be confirmed in skeletal muscle, heart and liver; 51 however, Hjv gene expression was clearly detectable in kidney and in smaller amounts in extrahepatic organs where it was downregulated. In non-HFE-HH, Hepc gene expression was reduced, 51,52 which suggests that Hjv could be involved in Hepc regulation; however, the mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 87%
“…7 Also, the ELISA used to measure the serum Hepc concentration was not specific for biologically active Hepc-25. 30,49 No practical assay has been reported for measurement of active Hepc-25, although attempts have been made to develop an assay system by using SELDI-TOF MS. 50 Hjv gene expression could be confirmed in skeletal muscle, heart and liver; 51 however, Hjv gene expression was clearly detectable in kidney and in smaller amounts in extrahepatic organs where it was downregulated. In non-HFE-HH, Hepc gene expression was reduced, 51,52 which suggests that Hjv could be involved in Hepc regulation; however, the mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 87%
“…The intensities of the two peaks corresponding to hepcidin-20 and hepcidin-25 were found to be higher in hemodialysis patients compared with healthy volunteers, and a correlation with serum ferritin was found. The authors also reported that hepcidin-25 levels did not seem to fall after a dialysis session in some of the patients (30).…”
Section: Surface Enhanced Laser Desorption/matrix-assisted Laser Desomentioning
confidence: 98%
“…Hepcidin determination in the serum of hemodialysis patients was carried out using SELDI (Ciphergen Biosystems, Freemont, CA), with a reported detection limit of 53 ng/ml (30). The intensities of the two peaks corresponding to hepcidin-20 and hepcidin-25 were found to be higher in hemodialysis patients compared with healthy volunteers, and a correlation with serum ferritin was found.…”
Section: Surface Enhanced Laser Desorption/matrix-assisted Laser Desomentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts to produce correctly folded synthetic hepcidin have proved difficult because the sequence contains eight cysteine residues that constrain the hepcidin molecule in a hairpin structure (Hunter et al 2002). Hepcidin in urine has also been quantified using mass spectrometry methods (Kemna et al 2005;Liang et al 2006;Tomosugi et al 2006).Prohepcidin, the sixty-amino-acid product of cleavage of the signal peptide from the hepcidin precursor, is expressed at the basolateral membrane domain of hepatocytes and is found in blood (Kulaksiz et al 2004). Serum prohepcidin concentrations are significantly lower in patients with hereditary haemochromatosis compared to healthy control subjects (Kulaksiz et al 2004), increase with declining kidney function (Taes et al 2004), and are correlated with haematocrit in chronic haemodialysis patients (Hsu et al 2006), but it is currently unclear whether * Corresponding author: Susan Fairweather-Tait, fax þ 44 1603 452578, email sue.fairweather-tait@bbsrc.ac.uk Abbreviations: DMT1, divalent metal transporter; sTfR, soluble transferrin receptor; LREC, local research ethics committee.…”
mentioning
confidence: 99%